2016
DOI: 10.1111/1475-6765.12131
|View full text |Cite
|
Sign up to set email alerts
|

Ripple effects: An exclusive host national context produces more perceived discrimination among immigrants

Abstract: This article examines the perceived discrimination of immigrants -a group for whom experiences of discrimination can be damaging for their long-term commitment and identification with the national core group. Taking its point of departure in the literature on national identity, the article argues that perceived discrimination should be strongest among immigrants in host national societies with an exclusive self-image. This hypothesis is examined by use of multilevel regressions on cross-national survey data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…However, at the level of individual attitudes, cross‐national surveys paint a picture in which Denmark is more typical: Larsen () found that Denmark is similar to most other North‐western European countries in his cross‐national typology of popular nationalism. Similarly, Simonsen () showed that Danes are quite similar to other North European peoples in their perceptions of the economic and cultural impacts of immigration. Finally, van der Waal, de Koster and van Oorschot () showed that welfare chauvinist attitudes are somewhat less prevalent in Nordic Europe than elsewhere (using the 2008 module of European Social Survey).…”
Section: Trust and Orientations Towards Diversitymentioning
confidence: 92%
“…However, at the level of individual attitudes, cross‐national surveys paint a picture in which Denmark is more typical: Larsen () found that Denmark is similar to most other North‐western European countries in his cross‐national typology of popular nationalism. Similarly, Simonsen () showed that Danes are quite similar to other North European peoples in their perceptions of the economic and cultural impacts of immigration. Finally, van der Waal, de Koster and van Oorschot () showed that welfare chauvinist attitudes are somewhat less prevalent in Nordic Europe than elsewhere (using the 2008 module of European Social Survey).…”
Section: Trust and Orientations Towards Diversitymentioning
confidence: 92%
“…Studies have shown that restrictive views of the nation (i.e., those based not only on elective but also ascriptive criteria, such as ancestry or birth in the country) are associated with stronger anti-immigrant attitudes (Kunovich 2009, Pehrson et al 2009, Wright 2011a; negative sentiments toward ethnic minorities (Citrin et al 1990); welfare chauvinism (Wright & Reeskens 2013); and cultural protectionism, including support for exclusionary language laws (Schildkraut 2003). These attitudinal outcomes are likely to have implications for the frequency and quality of social interaction across group boundaries, social movement mobilization, and support for exclusionary policies and extremist politics at the ballot box-though such causal effects have not been conclusively established in empirical research [but see Simonsen (2016aSimonsen ( , 2016b]. …”
Section: Who Is a Legitimate Member Of The Nation?mentioning
confidence: 99%
“…They are a combination of social exposure to actual discrimination and cognitive susceptibility to frame experiences in terms of discrimination Maxwell 2015). This explains intuitive findings, for instance, that persons of those origins who tend to be most rejected by natives report higher average levels of perceived discrimination (Habtegiorgis, Paradies, and Dunn 2014;Simonsen 2016). Another example is that immigrants who experience status loss (as compared to their country of origin) tend to suffer from depression over-frequently (Euteneuer and Schäfer 2018;Nicklett and Burgard 2009) and report more experiences of discrimination .…”
Section: Theoretical Backgroundmentioning
confidence: 97%